2016
DOI: 10.21608/jpp.2016.46168
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Coloration and Extending the Shelf Life of Plums While Alleviating Leaf Abscission by Utilizing Lisophosphatidylethanolamine and Oleic Acid

Abstract: Poor coloration of "Kelsey" plum fruits is considered one of the major problems that have been facing Egyptian growers, which hindered the expansion of "Kelsey" plum cultivation. Producers are in critical need to an effective treatment that enhances skin coloration while maintaining their keeping quality and their shelf life after harvest. Thus, the application of Ethrel, as an ethylene-releasing compound could increase anthocyanin content in plum skin. However, it has negative impact on leaf defoliation, yell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…On the other hand, all the used treatments lowered berry skin chlorophylls. The above trend of results whether for chlorophyll a or b agreed with those reported by Farag et al (2012) and Farag and Attia (2016). Ethephon stimulated the progressive loss of chlorophylls in apples (Huybrechts et al, 2003).…”
Section: Issn: 1110-0486supporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, all the used treatments lowered berry skin chlorophylls. The above trend of results whether for chlorophyll a or b agreed with those reported by Farag et al (2012) and Farag and Attia (2016). Ethephon stimulated the progressive loss of chlorophylls in apples (Huybrechts et al, 2003).…”
Section: Issn: 1110-0486supporting
confidence: 89%
“…Oleic acid is unsaturated fatty acid reported to advance fruit coloration and maintaining fruit quality of some fruit species such as apricotsand plums (Farag et al, 2012: Farag andAttia, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Treating fruits with LPE after AVG significantly increased fruit firmness due to LPE can maintain the plasma membrane integrity and mitigated the effect of ethylene on the cell wall or membranes lipid degradation (Farag and Palta, 1993a). Moreover, LPE retarded polygalacturonase-mediated fruit softening (Hong et al, 2008) and reduced activity of phospholipase D. The obtained results concerning this effect are in agreement with the findings of Farag and Attia (2016).…”
Section: Discussionsupporting
confidence: 71%
“…To explain the role of lisophos on apple fruit firmness, Farag and Attia, 2016 showed that preharvest spray of lisophos on plum fruit trees increased fruit firmness at harvest and keeping storability during storage. In the present study, lisophos spray showed positive effects on increasing fruit firmness (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Poor coloration has been a serious problem in affecting growers profit from these cultivars (Boyer and Liu, 2004). Lysophosphatidylethanolamine (LPE) such as lisophos is a natural lipid has been used as a coloring and ripening agent in many fruit crops such as apple, cranberry, tomato and plum (Farag andPalta, 1989, 1992 and Farag and Attia, 2016) while keeping fruit quality by either lowering the respiration rate, inhibiting the activity of cell wall hydrolyses and by retarding senescence (Farag and Palta, 1993). On the other hand, calcium plays an important role in maintaining the quality and storability of fruit (Bhat et al, 2012: Wehr et al, 2004.…”
Section: Introductionmentioning
confidence: 99%